2002
DOI: 10.1006/mthe.2002.0526
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of in Vivo DNA Electrotransfer: Respective Contributions of Cell Electropermeabilization and DNA Electrophoresis

Abstract: Efficient cell electrotransfection can be achieved using combinations of high-voltage (HV; 800 V/cm, 100 micros) and low-voltage (LV; 80 V/cm, 100 ms) pulses. We have developed equipment allowing the generation of various HV and LV combinations with precise control of the lag between the HV and LV pulses. We injected luciferase-encoding DNA in skeletal muscle, before or after pulse delivery, and measured luciferase expression after various pulse combinations. In parallel, we determined permeabilization levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
197
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(210 citation statements)
references
References 27 publications
11
197
0
2
Order By: Relevance
“…42 It was shown that the duration of the high permeabilized state of the muscle fibres was the same for the three combinations tested, all of them including the same HV pulse. On the contrary, the authors found that efficacy was only achieved if at least an LV was delivered after the HV.…”
Section: Roles Of the Electric Pulses In Dna Electrotransfermentioning
confidence: 93%
See 1 more Smart Citation
“…42 It was shown that the duration of the high permeabilized state of the muscle fibres was the same for the three combinations tested, all of them including the same HV pulse. On the contrary, the authors found that efficacy was only achieved if at least an LV was delivered after the HV.…”
Section: Roles Of the Electric Pulses In Dna Electrotransfermentioning
confidence: 93%
“…35,41,42 Moreover, for an efficient transfer, DNA must be injected before the electric pulses delivery. Thus, permeabilization of the cells is not sufficient even though it is necessary since efficient electrotransfer requires sufficiently intense electric fields (above cell permeabilization threshold).…”
Section: Roles Of the Electric Pulses In Dna Electrotransfermentioning
confidence: 99%
“…[10][11][12][13][14][15][16] A new protocol with high transfection efficacy in muscle and skin has recently been described, consisting of a combination of one high-field (HV, B1000 V cm À1 ) and one (or several) low-field (LV, B100 V cm À1 ) pulse. [17][18][19][20][21][22][23] For simplicity, we called all along the paper 'field' what indeed is the voltage to electrode width ratio, that is, an experimentally controlled parameter. In these studies, the authors suggested two functions of these electric pulses.…”
Section: Introductionmentioning
confidence: 99%
“…The 'HV' pulse permeabilizes the cells, whereas the 'LV' pulse drives plasmid DNA toward the cells and against the permeabilized membrane by the associated electrophoretic force. 19 In this new methodology, both types of pulses are necessary for successful gene expression in target cells, as described in the literature. The number of 'LV' pulses can vary, provided the overall duration of the pulses is kept constant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation